Ultrastructural Changes Associated with Reversible Stiffening in Catch Connective Tissue of Sea Cucumbers. - Masaki Tamori; Kinji Ishida; Eri Matsuura; Katsutoshi Ogasawara; Tomohito Hanasaka; Yasuhiro Takehana; Tatsuo Motokawa; Tokuji Osawa (PLoS ONE)
The dermis of sea cucumbers is a catch connective tissue or a mutable collagenous tissue that shows rapid, large and reversible stiffness changes in response to stimulation. The main component of the dermis is the extracellular material composed of collagen fibrils embedded in a hydrogel of proteoglycans. The stiffness of the extracellular material determines that of the dermis. The dermis has three mechanical states: soft (Sa), standard (Sb) and stiff (Sc). We studied the ultrastructural changes associated with the stiffness changes. Transverse sections of collagen fibrils in the dermis showed irregular perimeters with electron-dense protrusions or arms that cross-bridged between fibrils. The number of cross-bridges increased in stiffer dermis. The distance between the fibrils was shorter in Sc than that in other states, which was in accord with the previous report that water exuded from the tissue in the transition Sb→Sc. The ultrastructure of collagen fibrils that had been isolated from the dermis was also studied. Fibrils aggregated by tensilin, which causes the transition Sa→Sb possibly through an increase in cohesive forces between fibrils, had larger diameter than those dispersed by softenin, which antagonizes the effect of tensilin. No cross-bridges were found in isolated collagen fibrils. From the present ultrastructural study we propose that three different mechanisms work together to increase the dermal stiffness. 1.Tensilin makes collagen fibrils stronger and stiffer in Sa→Sb through an increase in cohesive forces between subfibrils that constituted fibrils; 2. Cross-bridging by arms caused the fibrils to be a continuous network of bundles both in Sa→Sb and in Sb→Sc; 3. The matrix embedding the fibril network became stiffer in Sb→Sc, which was produced by bonding associated with water exudation.